WELDABILITY STUDY OF AISI 1035 STEEL USING HYDRATED RB26 ELECTRODE BASED ON WIC TEST METHOD (AWS B4) - LENDISTANU, YUGA
In tropical regions where relative humidity is high throughout the year, ambient water vapor content will be rapidly picked up by welding electrode’s flux. Arc contaminated by hydrogen from the damp flux will increase risk of defects in welded joint, especially hydrogen cracking. In this work, weldability of AISI 1035 steel is studied based on Welding Insitute of Canada (WIC) Test and variation of moisture picked-up by Kobe Steel RB26 SMAW electrode (AWS A5.1 E6013) in a conditioned atmosphere. On the third day after welding, surface crack was examined using dye penetrant technique. In consequence of no preheat implemented, solidification cracking occured along 37% of the weld length although the flux was dried with 0% absorbed moisture relative to the flux’ weight, whereas more severe crack was found 48% on the sample welded using damp electrode with 7% absorbed moisture due to solidification and hydrogen effect. Preheat in 150°C minimalised risk of cracking which did not present on the sample welded by electrode containing 0% and 1.42% absorbed moisture, but crack still appeared (3%) on the sample welded using electrode having 1.83% absorbed moisture because of hydrogen contribution. As the one of analysis result, preheat in 150°C and 1.42% allowable absorbed moisture in the flux is recommended for the RB26 electrode.